ETIKA BERBUSANA ADAT KE PURA DALAM MEMBANGUN KARAKTER REMAJA DI DUSUN TAMBANG ELEH KABUPATEN LOMBOK BARAT - I Gede Jaya; I Gusti Lanang Ngurah Weda; Ida Bagus Kade Yoga Pramana (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Dressing is a freedom for everyone in expressing themselves, but the way of dressing is still bound to the norms that apply in society. Nowadays, there are many ways of dressing that follow the times that are considered inappropriate, such as how to dress in performing religious worship, this phenomenon is generally found in the younger generation who are categorized as teenagers. Based on this, the researcher is interested in taking research action related to traditional dress ethics in shaping the character of adolescents in the hamlet of Tambang Eleh, West Lombok Regency, considering that this location is one of the places that has quite a lot of Hindus compared to other places. This study aims to describe the phenomenon of traditional dress ethics to the temple in building the character of adolescents in Dusun Tambang Eleh. This research is descriptive qualitative using observation, interview and documentation methods. This research uses behavioristic learning theory and symbolic interactionism theory. The results of this study are as follows: The customary dress ethics to the temple applied by teenagers in Dusun Tambang Eleh are in accordance with Hindu ethics / precepts, namely clean, neat, and polite, but there are some teenagers who still do not understand and do some deviations in dress ethics. As well as some teenage characters that can be formed in the application of dress ethics, namely religious character, discipline, and responsibility for themselves.